2014
DOI: 10.1590/s0100-40422014000100025
|View full text |Cite
|
Sign up to set email alerts
|

Otimização, validação e aplicação de método para determinação da concentração residual de difenoconazol em morangos após múltiplas aplicações

Abstract: fruit cultivated in pots were estimated using the solid-liquid extraction with low temperature partition (SLE/LTP) method for sample preparation and gas chromatography with electron capture detection (GC/ECD) for analysis. The optimized method presented excellent recovery values from fortified samples and reproducibility (average recovery values ≥ 98%; CV values ≤ 15%). Linearity of response was demonstrated (r = 0.995) with a detection limit of 9 µg kg -1 . The method was successfully applied for the determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…Heleno et al (2014a) and Freitas et al (2014) also evaluated the effect of freezing time on the chromatographic response of pesticides. Heleno et al (2014b) observed that there was no influence on the chromatographic responses when the freezing time ranged between 5 and 12 h. However, Freitas et al (2014) achieved results, in that the freezing of 3 h provided better chromatographic responses (areas) of pesticides in corn through SLE-LTP. Vieira, Neves, and Queiroz (2007), obtained contradictory results regarding the solvent extractor volume, in which the increase of the proportion of the solvent acetonitrile volume in relation to the sample volume, from 1:1 to 1:2 (v/v) (sample/acetonitrile), increased the extraction yield from 11 % to λ-cyhalothrin, and 7 % for cypermethrin in water by liquid-liquid extraction with partition at low temperature (LLE-LTP).…”
Section: Factorial Planning 2mentioning
confidence: 93%
See 1 more Smart Citation
“…Heleno et al (2014a) and Freitas et al (2014) also evaluated the effect of freezing time on the chromatographic response of pesticides. Heleno et al (2014b) observed that there was no influence on the chromatographic responses when the freezing time ranged between 5 and 12 h. However, Freitas et al (2014) achieved results, in that the freezing of 3 h provided better chromatographic responses (areas) of pesticides in corn through SLE-LTP. Vieira, Neves, and Queiroz (2007), obtained contradictory results regarding the solvent extractor volume, in which the increase of the proportion of the solvent acetonitrile volume in relation to the sample volume, from 1:1 to 1:2 (v/v) (sample/acetonitrile), increased the extraction yield from 11 % to λ-cyhalothrin, and 7 % for cypermethrin in water by liquid-liquid extraction with partition at low temperature (LLE-LTP).…”
Section: Factorial Planning 2mentioning
confidence: 93%
“…Similar results were found by Freitas et al (2014), who observed that the agitation time in the vortex showed no significance within the limits studied for extraction of insecticides by SLE-LTP in stored corn,. However, Heleno et al (2014b) reported that the agitation time on the agitator table significantly affected the difenoconazole extraction by SLE-LTP in strawberry. Heleno et al (2014a) and Freitas et al (2014) also evaluated the effect of freezing time on the chromatographic response of pesticides.…”
Section: Factorial Planning 2mentioning
confidence: 96%
“…O método permite o desempenho simultâneo pela extração de agrotóxicos e limpeza dos extratos e inúmeros estudos também já foram realizados, sendo aplicado em amostras frutíferas e de origem vegetal, como na batata [22], cenoura [23], abobrinha [24], alface [25], alho [26], milho [27], tomates [28], cajá-manga [29], pimentão [30] e aplicado em amostras de solos [31][32][33]. O método é simples, eficiente, oferece praticidade, baixo consumo de solvente orgânico e amostra, número reduzido de etapas e confiabilidade com porcentagens de recuperação elevadas e boa repetitividade [34].…”
Section: ____________________________________________________________unclassified
“…Vários trabalhos são encontrados na literatura a fim de demonstrar a eficiência da ESL-PBT para a determinação e quantificação de resíduos de agrotóxicos em matrizes alimentícias. A ESL-PBT foi otimizada e validada para a determinação de multiresíduos em casca e em polpa de banana (Hernández, 2015), para a determinação dos agrotóxicos procimidona, haloxyfop-metil e linuron em cenoura (Lara, 2014), e ainda utilizado para determinação de resíduos do pesticida difenoconazol em morangos (Heleno, 2014).…”
Section: Metodologiaunclassified
“…Os limites de quantificação (LQ) e detecção (LD) representam a menor concentração de analito que pode ser detectada e determinada em um nível específico de confiança, ou seja, pode-se encontrar um menor valor detectável e junto a ele analisar um nível mínimo de quantificação em que o método é aceitável e aplicável (Heleno, 2014).…”
Section: Limite De Quantificação (Lq) E Limite De Detecção (Ld)unclassified